Lincoln's last days : the shocking assassination that changed America forever - O'Reilly, Bill; Zimmerman, Dwight Jon; O'Reilly, Bill (New York : Henry Holt and Co., 2012)
Describes the events surrounding the assassination of Abraham Lincoln and the hunt to track down John Wilkes Booth and his accomplices.
The beginning of the end of the war -- The conspiracy to assassinate -- Lincoln's last day -- Chasing the assassins -- Afterward -- Epilogue -- Excerpt from Harper's weekly, April 29, 1865 -- Finding Lincoln in today's Washington, D.C -- Visual glossary -- Abraham Lincoln timeline -- John Wilkes Booth timeline -- Recommended reading -- Recommended websites.
Keywords: Lincoln, Abraham -- 1809-1865 -- Assassination